The bonn agreement and making of democracy in Afghanistan - Ra'ees, Wahabuddin (2007)
During the American-led military campaign, the anti- Taliban Afghan groups signed the .UNsponsored December 5,200 I, Bonn Agre~ment in Germany. The Agreement in addition to the formation of the post- Taliban interim administration also provided a comprehensive framework for the democratization of Afghanistan. This study examines the process of democratization in Afghanistan initiated by the Bonn Agreement. First, it reviews the process of institution-building by the post- Taliban administration. Then it discusses the issues of ideology, ethnic cleavages, women, partisan politics and the role of Islam and the Islamists brought about by the democratization debate. Afghanistan's past history suggests that there exists a positive relationship between the absence of democracy, extremism and violent political conflict. Therefore, the study finally concludes that democratization of Afghanistan has the potential of moderating the negative impact of the 'ideological and ethnic divides' within the Afghan society.